Physical, Physiological and Psychological Fitness of Independent Active and Non-Active Older Female Adults (Baltic Journal of Sport and Health Sciences, 2015)
Background. Aging represents period of life when human body undergoes great changes affecting people’s condition and overall health. The aim of the research was to determine differences of motor and functional abilities along with satisfaction and quality of life between active and non-active female older adults.Methods. Twenty-one elderly female adults were classified in two groups: thirteen active (mean age 66.54  ± 4.59 years; mean height 158.08± 5.35 cm; mean weight 75.47 ± 13.52 kg; mean body mass index 30.18 ± 0.49 kg/m 2 ) and eight non-active (mean age 71.81 ± 7.15 years; mean height 160.55 ± 6.34 cm; mean weight 74.40 ± 14.06 kg; mean body mass index 28.84 ± 0.35 kg/m 2 ) female adults. For the purpose of this study, all participants were asked to complete senior fitness test protocol prescribed by Rikli and Jones (2013), which consisted of eight tests: 30-second chair stand test, 30-second arm curl test, 2-minute step test, chair sit-and-reach test, back scratch test, 8-foot up-and-go test, height and weight. Along with that, participants filled in Croatian version of WHOQOL-BREF questionnaire (Pibernik-Okanović, 2001) including four domains (physical health, psychological health, social environment and environment) with two additional questions about their satisfaction with health and their quality of life on the Likert scale ranging from 1to 5. The differences between active and non-active groups were examined using Man-Witney U-test. Significance was set at p < .05.Results. Results showed significant differences in four fitness tests: 30-second arm curl test (p = .03), 2-minute step test (p = .00), chair sit-and-reach test (p = .02), 8-foot up-and-go test (p = .01) and two questionnaire domains: psychological health (p = .04) and environment (p = .01). No statistical differences were found among perception of the quality of life and health satisfaction between non-active and active participants (p > .05).Conclusion. This study showed that older female adults had better achievements in motor and psychological tests, which could be translated to better physical overall fitness and preparedness of doing everyday activities in comparison to non-active group. Research showed the importance of exercising in older age, but further studies on bigger samples need to be performed for better understanding of aging and differences in levels of fitness.Keywords: geriatrics, conditioning abilities, satisfaction with life, aging.